A case study of using the hybrid model of scrum and six sigma in software development - Mona Najafi Sarpiri; Taghi Javdani Gandomani (Institute of Advanced Engineering and Science, 2021)
The world of software engineering is constantly discovering new ways that lead to an increase in team performance in the production of software products and, at the same time, brings the customer's further satisfaction. With the advent of agile methodologies in software development, these objectives have been considered more seriously by software teams and companies. Due to their very nature, agile methodologies have the potential to be integrated with other methodologies or specific managerial approaches defined in line with agility objectives. One of the cases is Six Sigma, which is used in organizations by focusing on organizational change and process improvement. In the present study, attempts were made to present the hybrid software development approach, including Scrum, as the most common agile and Six Sigma methodology. This approach was practically used in a case study, and the obtained results were analyzed. The results of this evaluation showed that this hybrid method could lead to the increased team performance and customer satisfaction. However, besides these two achievements, an increase in the number of re-works, number of defects discovered, and the duration of the project implementation were also observed. These cases are in line with the main objectives of Scrum and Six Sigma and are justifiable and acceptable due to achieving those objectives.